EFFECTS AND SUCCESS FACTORS OF ENTERPRISE RESOURCE PLANNING IMPLEMENTATION ON ORGANIZATIONAL PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Widjaja, Marco; Sardjono, Wahyu (Universitas Nusa Cendana, 2024)
The rapid development of information technology today has prompted organizations or companies to invest in and implement information technology. Enterprise Resource Planinng (ERP) implementation is one such investment or information technology-related implementation. ERP implementation is carried out to assist organizations or companies in achieving their business goals. However, implementing ERP within an organization or company is not an easy task and comes with consequences that must be faced if the implementation fails. This study wants to identify the elements that affect whether ERP installation within businesses or organizations is successful or unsuccessful. This study also seeks to comprehend the effects of successful or unsuccessful ERP implementation within businesses or organizations. This study conducts a review of the literature concerning ERP implementation within organizations or companies. In accordance with the literature evaluation done for this study, user training, top management support, and vendor support are the three areas that have been extensively investigated in the context of implementing an ERP, all of which impact the success or failure of the whole process. Performance inside an organization is affected by both the success and failure of ERP adoption. This performance enhancement extends not only to the organization but also to the performance of the employees working within it. Apart from the advantages of successful ERP implementation, ERP implementation can also fail. Failures in the deployment of ERP can cause organizations or businesses to lose money on their information technology investments. Keywords: Enterprise Resource Planning; ERP Success Factor; ERP Implementation Impact, Organization Performance; Unsuccessful ERP